THE INFLUENCE OF EMPLOYEE ENGAGEMENT, SPIRITUAL LEADERSHIP AND ISLAMIC WORK ETHIC ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN THE POLICE FORCE PAMONG PRAJA AND WILAYATUL HISBAH BIREUEN DISTRICT - Pipi Santika; Marbawi; Faisal Matriadi; Yusniar (RADJA PUBLIKA, 2024)
This research was conducted to examine the influence of employee engagement, spiritual leadership and Islamic work ethic on organizational citizenship behavior (OCB) in the Bireuen Regency Civil Service and Wilayatul Hisbah Police Unit. The population in this study were employees in the civil service and wilayatul hisbah police units in Bireuen Regency, totaling 204 employees. Meanwhile, the number of samples in this study was 67 employees. The data collection technique used was a survey technique through distributing questionnaires. The data analysis method used is multiple regression analysis technique using SPSS 25. Data analysis uses the classic assumption test, partial test (t) and coefficient of determination test. The research results show that employee engagement, spiritual leadership and Islamic work ethic have a positive and significant effect on Organizational Citizenship Behavior (OCB) in the Bireuen Regency Civil Service and Wilayatul Hisbah Police Unit.